Clinical report: the joint obstetric and psychiatric management of phobic anxiety disorders in pregnancy. (March 2015) - Patel, Roshni R.; Hollins, Kathryn
Abstract: Women who struggle with distressing pregnancy-related phobic anxiety disorders are regularly encountered in maternity services, and their management poses particular challenges. Early identification is crucial in order to offer an opportunity to treat and manage their fears and enable a positive birth experience. In this article, women with different phobias (tokophobia, emetophobia and ante-cubital fossa phobia) describe their first pregnancy experience, and the ways in which the Chelsea and Westminster Hospital offered them joint maternity and psychiatric care. A multidisciplinary hospital-based approach can be effective in managing mental health problems in pregnancy. Despite maternal preconceptions and professional misgivings, this approach can work for women with phobias and enable a good birth experience and successful mother and infant bonding. The lead obstetrician for mental health and perinatal psychiatrist describe their roles in enabling successful outcomes for both the current and subsequent pregnancies. The case is made for training of maternity staff in both the identification of severe pregnancy phobias and the prompt referral for shared psychiatric and maternity care. Even if previous treatments have failed, adequate coping strategies for childbirth may be achieved in a short time frame. Long-term improvements in the phobia itself may also be found.